Hammett Acidity Function for Mixed ZrO2–SiO2 Oxide at Elevated Temperatures - E. I. Inshina; D. V. Shistka; G. M. Telbiz; V. V. Brei (Хімія, фізика та технологія поверхні, 2012)
The mixed ZrO2?SiO2 oxides with different 4 ? Zr/Si ? 0.25 atomic ratios have been prepared using a sol-gel method. It was shown that the concentration-strength acid site distributions on the surface of ZrO2?SiO2 are caused by Zr4+/Si4+ ratio. The ZrO2?SiO2 with Zr/Si = 0.5 is characterized by the highest strength of acid sites (Н0 = –11.35). According to the IR-spectra of adsorbed pyridine, the B- and L-acid sites are present in the ZrO2?SiO2 samples with Zr/Si<1 whereas at Zr/Si>1 only L?sites are formed. Basing on the UV-Vis diffuse reflectance spectra of adsorbed indicators, the H0 values for ZrO2?2SiO2 have been determined at elevated temperatures. The Hammett acidity function reaches the superacid value of Н0 ? –14.5 at Т ? 85 °С.